DIVERSIFICATION OF ECONOMY – AN INSIGHT INTO ECONOMIC DEVELOPMENT WITH SPECIAL REFERENCE TO KURDISTAN’S OIL ECONOMY AND AGRICULTURE ECONOMY - Pankaj D.; Ramyar R.A. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
Diversifying economy from one sector to another is a vital problem faced by many nations across the globe. Many countries believe that economic development is achieved by diversifying the economy by switching the major revenue sectors. The main objective of this research paper is to study the economic development of Kurdistan region through diversification from Oil to agriculture economy and one more objective is to find out how the role of FDI will create the impact over the growth of economy in agriculture sector. The study is concentrated on 50 agriculturists through convenience sampling method. Kurdistan is an autonomous province in Iraq which is heavily dependent on oil sector for its major part of revenue. On the other hand it is ignoring agriculture sector which has a great potential to earn heavy revenue for the country. This paper reveals that, the Agriculture can play the major role in the economic development of Kurdistan in future as an employment generation, increase in GDP, Increase in Government revenue and diversify development. This research paper proposes some financial model for the possible growth of agriculture sector along with agro technology through small investor FDI scheme and Agriculture insurance scheme. From this study, it is found that if proposed suggestion is been concentrated on agriculture by KRG surely GDP will increase.